2020
DOI: 10.3390/met10101283
|View full text |Cite
|
Sign up to set email alerts
|

Initial Corrosion Behavior of 12Cr1MoV Steel in Thiosulfate-Containing Sodium Aluminate Solution

Abstract: When alumina is produced by the Bayer process with high-sulfur bauxite, the sulfur would strongly corrode the 12Cr1MoV steel made heat exchanger. This study investigated the initial corrosion behavior of the 12Cr1MoV steel exposed to a thiosulfate-containing sodium aluminate (TCSA) solution under the evaporation conditions of alumina production. The obtained corrosion rate equation is V = 6.306·t·exp(−0.71). As corrosion progressed, with the corrosion product film growing, the corrosion current density decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the middle and later stages of corrosion, the corrosion products continue to react with the ions. On the one hand, the formation of structurally stable iron oxide causes surface pseudo-passivation, as shown in Equations ( 7)-( 13) [14,26,28], and on the other hand, the ionization of FeS occurs, as shown in Equation ( 14) [14,48]. These electrode reactions correspond to the anode pseudo-passivation zone of the polarization curves (Figure 7).…”
Section: Formation Mechanism Of Surface Corrosion Productsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the middle and later stages of corrosion, the corrosion products continue to react with the ions. On the one hand, the formation of structurally stable iron oxide causes surface pseudo-passivation, as shown in Equations ( 7)-( 13) [14,26,28], and on the other hand, the ionization of FeS occurs, as shown in Equation ( 14) [14,48]. These electrode reactions correspond to the anode pseudo-passivation zone of the polarization curves (Figure 7).…”
Section: Formation Mechanism Of Surface Corrosion Productsmentioning
confidence: 99%
“…A mathematical fitting was performed to determine the mathematical relationship between the corrosion rate and the corrosion time, and it was found that the corrosion rate satisfied the mathematical model of the power function at the initial stage of corrosion [28][29][30], which is shown in Table 2, and the fitting curve is shown in Figure 6a. The fitting correlation coefficients in Table 2 are basically above 0.9, indicating that the fitting equation of corrosion dynamics of the Q235 steel has a good correlation with the experimental results.…”
Section: Corrosion Ratementioning
confidence: 99%
See 2 more Smart Citations
“…9,10 With the recycling of alumina production, it is found that the steel has serious selective corrosion, pitting corrosion, corrosion cracking, and uniform corrosion. 11,12 In the production process of Bayer alumina, the different alumina production processes need to be completed at different temperatures, for example, the seed crystal decomposition temperature is 65 °C, the evaporation temperature is 110 °C, and the dilution temperature is 95 °C, approximately. 13 Therefore, the study of the corrosion behavior of corrosion temperature on the tank material is of great significance to material protection and material selection.…”
Section: Introductionmentioning
confidence: 99%